Pengaruh Pengetahuan Perpajakan, Modernisasi Sistem Administrasi Perpajakan, Tax Amnesty, Tingkat Penghasilan Pada Kepatuhan Wajib Pajak - Wiranatha, Hadi; Rasmini, Ni Ketut (E-Jurnal Akuntansi; Vol 21 No 3 (2017)DO - 10.24843/EJA.2017.v21.i03.p25, 2017)
Indonesia as a developing country is intensively carrying out development. target the government  to improve the people's economy from Micro, Small and Medium Enterprises. Micro Small and Medium Enterprises is a populist economy based on the economic people power to manage the resources to move economy in the area . In Jembrana Regency, corporate taxpayer compliance sector UMKM under 50% is still very low. The purpose of this study was to test the tax knowledge, modernization in taxation administration system, tax amnesty and income level in corporate taxpayer compliance sector UMKM in Jembrana. The population in this study is the corporate taxpayer effectively on KPP Pratama Tabanan with total 1.239 Taxpayer. Based on the population, the sample in this study is 100 corporate Taxpayers are calculated using the Slovin formula. The data collection technique used was accidental sampling in accordance with the criteria of sampling. The data corporate taxpayer from KPP Pratama Tabanan because Jembrana regency entered working area of ??KPP Pratama Tabanan. Data analysis techniques in this study using multiple linear regression analysis. The result shows that the tax knowledge, modernization in taxation administration system, tax amnesty and income level positively influence on corporate taxpayer compliance sector UMKM in Jembrana regency.      Keywords:  tax     knowledge,    modernization  in   tax   administration  system, tax amnesty,                           income level